2021
DOI: 10.3390/su13126810
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility Strategies in Spanish Electric Cooperatives. Analysis of Stakeholder Engagement

Abstract: Cooperative organizations try to balance economic viability and corporate social responsibility (CSR) management through strategic policies that involve dialogue, participation, and engagement with stakeholders. To measure the impact of CSR management, the electricity sector implements monitoring processes and models, such as the sustainability reporting standards of the Global Reporting Initiative (GRI), which measure contributions to the Sustainable Development Goals (SDGs) of the United Nations 2030 Agenda.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The resulting strong ties between the directors and the community accords with previous literature, which states that the CSR approach of cooperatives is strongly linked with their communities' expectations [49]. Expanding on the literature, which emphasizes the importance of dialogue, participation, and engagement with stakeholders [32], our results suggest that directors influence CSR strategy through the importance they give to meeting members' needs. Indeed, our results show that in rural areas, with members who have needs directly related to the use of the territory, more proactive strategies are adopted with regard to the environmental dimension than financial cooperatives established in urban areas.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The resulting strong ties between the directors and the community accords with previous literature, which states that the CSR approach of cooperatives is strongly linked with their communities' expectations [49]. Expanding on the literature, which emphasizes the importance of dialogue, participation, and engagement with stakeholders [32], our results suggest that directors influence CSR strategy through the importance they give to meeting members' needs. Indeed, our results show that in rural areas, with members who have needs directly related to the use of the territory, more proactive strategies are adopted with regard to the environmental dimension than financial cooperatives established in urban areas.…”
Section: Discussionsupporting
confidence: 85%
“…As social enterprises, cooperatives inevitably pursue both economic and social goals [3,21,22,32]. Consequently, it is reasonable to expect cooperatives to be actively committed to CSR as part of their activities [2,30,[33][34][35].…”
Section: Cooperatives and Csrmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding stakeholders' perspectives, stakeholder engagement is essential for implementing CSR strategies and achieving SDGs [45,64,65]. Stakeholder theory can be used to explain how corporations engage in SDG disclosures.…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%
“…Small and medium-sized enterprises (SMEs) are not free from corporate social responsibility, as [10] notes. Previous research found that the majority of social economy businesses have not developed CSR programmes that link to their most key SDGs and sustainability as a social obligation [11].…”
Section: Introductionmentioning
confidence: 99%